The Relationship Between Sense of Calling, Moral Sensitivity, Attitude Toward Death and Attitude Toward End-of-life Nursing of Nursing Students Ahead of Graduation - Oh, Jae Woo; Kim, Mi-Ran (International Journal of Membrane Science and Technology, 2023)
This study was attempted to grasp the relationship between sense of calling, moral sensitivity, and attitude toward death, and attitude toward end—of-life nursing of nursing students ahead of graduation and to provide the basic data for developing education program to enhance the proper attitude of end-of-life nursing based on human dignity. Methods: The data collection period was from April 01, 2020 to April 4, 2020. The survey was conducted on 165 nursing students who were expecting to graduate from the nursing college located in D city. Result: The factors which affect the end-of-life nursing attitude of nursing students were attitude toward death, moral sensitivity, and type of practice institutions, and the explanatory power of these variables for end-of-life nursing attitude was 22.2%. Conclusion: It is necessary to expand an opportunity for indirect experience of end-of-life nursing that must be performed as a nurse to nursing students who are about to graduate, and various educational program development and implementation strategies are required to establish a sense of mission and the good awareness of death.